2013
DOI: 10.7763/ijbbb.2013.v3.171
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Pequi and Guavira Fruit Wastes via Solid State Bioprocess Using Pleurotus Sajor-Caju

Abstract: Abstract-Fungal microorganisms are widely studied in the bioconversion of substrates. Among them, Pleurotus sajor-caju is well recognized for its known ability to colonize and degrade wastes through solid state bioprocess (SSB). Fruit residues are inexpensive substrates that present characteristics favorable for microorganisms' colonization. The aim of this work was to investigate the mycelial growth of P. sajor-caju on pequi and guavira fruit wastes through SSB, in order to valorize these residues by their bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 24 publications
(20 reference statements)
0
18
0
1
Order By: Relevance
“…CMCase activities in the range of 3 to 4 U/g were found on both pequi and guavira substrates with the fungos P. sajor-caju (Silva et al 2013). The same authors found also no xylanase activity on pequi waste substrate, but showed 4.67 U/g activity in substrate composed with guavira residues.…”
Section: Enzyme Activity Analysismentioning
confidence: 60%
See 4 more Smart Citations
“…CMCase activities in the range of 3 to 4 U/g were found on both pequi and guavira substrates with the fungos P. sajor-caju (Silva et al 2013). The same authors found also no xylanase activity on pequi waste substrate, but showed 4.67 U/g activity in substrate composed with guavira residues.…”
Section: Enzyme Activity Analysismentioning
confidence: 60%
“…The authors classified these residues as potential good substrates for alpha amylases (Khan and Yadav, 2011). However, much higher amylase activities were observed for both pequi and guavira waste substrates in solid state bioprocesses with P. sajor-caju (Silva et al 2013). For pequi waste substrate the authors found a higher production (9.4 U/g) after 20 days of cultivation.…”
Section: Enzyme Activity Analysismentioning
confidence: 75%
See 3 more Smart Citations